Pkm Pengelolahan Ayam Layer Kelompok Perempuan Di Desa Paddinging Kecamatan Sandrobone Kabupaten Takalar - Kamase, Jeni; Hamzah, Fyrdha Faradyba; Taufan, Rezky Ratnasari (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2023)
The target of this PKM is a group of layer chicken breeders in Paddinging village. One of the objectives of the PKM to be achieved is to build a community group that is economically independent. To realize the objectives of the PKM, the partner group whose orientation is community groups who are interested in entrepreneurship. In this program, the women's group that is used as a partner group is the Sigunakannga group, which consists of 7 members. The partner group as layer chicken breeders and housewives do not understand/know the management of layer chickens into products that provide selling value as long as the chickens are still alive through traditional markets or partners.